Multifunctional K-band scanning radiometer with an additive noise pilot signal - Войтович, О.А.; Линкова, А.М.; Могила, А.А.; Мальцев, В.П.; Руднев, Г.А.; Хлопов, Г.И.; Грибский, О.П.; Маковенко, С.В.; Мальцев, С.Б.; Миронюк, С.В.; Павленко, В.Д. (Radiotekhnika, 2019)
A variant of the construction of a radiometer with a stochotic pilot signal is considered, in which a logarithmic detector of root-mean-square values is used instead of a quadratic one, which made it possible to obtain a dynamic range of the radiometer over 60 dB. It was experimentally shown that the developed Ka-band scanning radiometer at a distance of about 200 m has a resolution of about 4 m in field images and in the raster scan mode in angular coordinates it allows to obtain radio-thermal images of the observed sky section or underlying surface.